Chemical Composition and Antimicrobial Activity of Oliveria decumbens Volatile Oil from West of Iran - H Hajimehdipoor; N Samadi; V Mozaffarian; N Rahimifard; Sh Shoeibi; M Pirali Hamedani (Institue of Medicinal Plants, ACECR, 2010)
Background: Oliveria decumbens Vent. is an endemic plant of Flora Iranica that grows in high temperature areas of south and west of Iran. It is used for indigestion, diarrhea, abdominal pain and fever in traditional medicine.   Objective: In this investigation, chemical composition and antimicrobial effects of Oliveria decumbens has been studied.   Methods: The essential oil of aerial parts of Oliveria decumbens was obtained by hydrodistillation and analyzed by GC-MS. The antimicrobial activity of the essential oil was also investigated against three Gram positive bacteria, two Gram negative bacteria and two fungi using disc diffusion method.   Results: 10 components were identified in the essential oil of Oliveria decumbens. The main components were γ-terpinene, myristicin, thymol, ρ-cymene and carvacrol. The essential oil showed high antimicrobial activity against Gram-positive bacteria, Escherichia coli, Aspergilus niger and Candida albicans but low antibacterial effect against Pseudomonas aeroginosa. Conclusion: High amount of thymol, carvacrol and ρ-cymene in Oliveria decumbens essential oil may be a reason of antimicrobial effects of the plant and the plant essential oil can be considered as a natural source of preservatives in food and cosmetic industries.